Maslahah Mursalah dalam Praktik Yudisial: Studi Kasus Putusan Hakim Pengadilan Agama Sungguminasa 2023-2024 Terkait Harta Bersama Pasca Perceraian - Andi Syahru Ramadhan; Kurniati; Asni; Supardin; Rusdi Tahir (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This study aims to reveal a description of the 2023–2024 joint property division case at the Sungguminasa Religious Court, the basis for the judge's considerations in deciding the case, and the application of the maṣlaḥah mursalah principle in the decision-making process. The approach used is empirical juridical through documentation studies and interviews with judges. This type of research uses qualitative research, which is a data collection that is carried out objectively and analyzes data to improve and test a problem. This research was conducted at the Sungguminasa Religious Court Class I A. The results of the study show that the description of cases in 2023-2024 shows a downward trend compared to previous years. The basis for the judge's considerations considers not only the provisions of Law No. 1 of 1974, the Compilation of Islamic Law, and the Civil Code, but also aspects of the contribution of each party in obtaining property during the marriage. Applying the perspective of maṣlaḥah mursalah, the judge's decision is directed at efforts to protect parties who are more vulnerable economically and socially, to avoid harm, and achieve proportional justice.